Steam explosion pretreatment and enzymatic saccharification of duckweed (Lemna minor) biomass. (January 2015) - Zhao, X.; Moates, G.K.; Wilson, D.R.; Ghogare, R.J.; Coleman, M.J.; Waldron, K.W.
Abstract: Our previous research has shown that duckweed is potentially an ideal feedstock for the production of biofuels because it can be effectively saccharified enzymatically. Here we report the results of experiments in which duckweed was pre-treated by steam explosion prior to enzyme digestion. A range of temperatures, from 130 to 230 °C with a fixed retention time of 10 min, were employed. The best pretreatment conditions were 210 °C for 10 min; these conditions produced the highest amount of water-soluble material (70%), the greatest levels of starch solubilisation (21%) and hemicellulose and pectic polysaccharides degradation (60%). The use of these steam explosion conditions enabled large reductions in the concentrations of enzymes required for effective saccharification. The amount of Celluclast required was reduced from 100 U (4.35 FPU) g −1 substrate to 20 U g −1 substrate, and additional beta-glucosidase was reduced from 100 to 2 U g −1 substrate. Highlights: Consideration of duckweed as a potential feedstock for bioethanol production. Starch (21% by dry matter) is solubilised by steam explosion of duckweed. Steam explosion results in hydrolysis (60%) of hemicellulose & pectin. Low concentrations of fermentation inhibitors are produced upon steam explosion. Very low enzyme dosages can be employed to hydrolyse steam exploded biomass.